Beyond psychiatry: motivations for considering an Australian wellbeing program within Malaysian health services. (June 2019) - Silim, Umi Adzlin; Suhaimi, Aida Farhana; Moore, Gaye; Ryan, Brigid; Castle, David J
Objectives: To explore the relevance and adaptability of the Optimal Health Program for mental and primary healthcare providers in Malaysia. Methods: Evaluate stakeholder engagement and training programme for psychiatrists, family medicine specialists, public health specialists, physicians, clinical psychologists, counsellors, and representatives from a patient support group. Evaluate the programme for applicability, as well as participant's knowledge and confidence in using key components. Results: The training was very well received in terms of content, training materials and facilitation style. Development of culturally specific materials will be needed. Improvement in the self-rating measurement for knowledge and confidence in using key Optimal Health Program components was reported at the completion of the 2-day training. Conclusions: The Optimal Health Program has potential as a comprehensive socio-culturally responsive self-management programme that is relevant within mental health services and adaptable for task-sharing of mental health care in Malaysia.